2015
DOI: 10.1007/s10834-015-9447-2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Behavior and Attitudes of Asians Compared to Other Racial/Ethnic Groups in the United States

Abstract: Most research studying family financial behavior of racial/ethnic groups has ignored Asian households or arbitrarily combined them with other racial/ethnic groups. We treated Asian households as a separate racial/ ethnic group to compare twelve financial behaviors and attitudes of Asian households to those of three other racial/ ethnic groups: White, Black and Hispanic. Using multivariate analyses with the 2010 Survey of Consumer Finances, we found differences in seven behaviors/attitudes between Asian househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Relational aggression at Wave 2 was controlled to estimate the autoregressive stability effects, and we also considered covariance among husbands' and wives' intercepts (i.e., levels at T2) and slopes (i.e., changes across T2/3/4) of marital power. We assessed and included control variables—which were found to be associated with key study constructs in the present study (Hanna et al, 2015; LeBaron et al, 2019; Powers & Kaukinen, 2012). For each couple, before‐marriage cohabitation was assessed with a binary variable (0 = did not cohabit with the current partner before marriage vs. 1 = cohabited with the current partner before marriage).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Relational aggression at Wave 2 was controlled to estimate the autoregressive stability effects, and we also considered covariance among husbands' and wives' intercepts (i.e., levels at T2) and slopes (i.e., changes across T2/3/4) of marital power. We assessed and included control variables—which were found to be associated with key study constructs in the present study (Hanna et al, 2015; LeBaron et al, 2019; Powers & Kaukinen, 2012). For each couple, before‐marriage cohabitation was assessed with a binary variable (0 = did not cohabit with the current partner before marriage vs. 1 = cohabited with the current partner before marriage).…”
Section: The Present Studymentioning
confidence: 99%
“…For husbands and wives, marital history was assessed with a binary variable (0 = in first marriage vs. 1 = been married before). Age at marriage was assessed with an open‐ended question: “How old were you when you married your current spouse?” Race/ethnicity was assessed using four dummy codes (0 = White vs. 1 = Black; 0 = White vs. 1 = Asian; 0 = White vs. 1 = Latino; 0 = White vs. 1 = other race/ethnicity; Hanna et al, 2015).…”
Section: The Present Studymentioning
confidence: 99%
“…They have a lower rate of sexually transmitted diseases [4], a lower level of risky driving behavior [5], and lower transport mobility than their American counterparts [6]. Asian households have a lower credit delinquency rate compared to other racial/ethnic groups in the United States [7], and the Asian-Pacific region maintains a high average rate of gross domestic saving [8]. Also, Asian countries approach global governance largely in terms of selfhelp [9].…”
Section: Introductionmentioning
confidence: 99%
“…This trend is primarily seen in African American households (Fang et al, 2013;Stevenson & Plath, 2002), which have progressed over the past century and a half in pursuing financial independence; some have already achieved this, while the majority still work toward it. Previous studies have found that some segments of the African American population still experience the burden of restrictive financial obligations and low stock ownership (Hanna et al, 2012(Hanna et al, , 2015Herbert et al, 2005), low homeownership, and an average income barely above the poverty benchmark (Hanna & Lindamood, 2008).…”
mentioning
confidence: 99%
“…Understanding differences in national generational cohorts is essential when studying the financial well-being of households striving to achieve security (Hanna et al, 2015). Previous research has uncovered a considerable divide between African American and White households (Fang et al, 2013;Hanna & Lindamood, 2008;Hanna et al, 2015;Herbert et al, 2005).…”
mentioning
confidence: 99%